Neuroprotective potential of Myrica esulenta in Haloperidol induced Parkinson's disease - Kabra, A (2020)
Background: Myrica esculenta is a notable therapeutic plant widely utilized in Indian system of medicine. Ayurvedic literature reported fruit and bark of this plant is used in gulma, jvara, arsa, grahani, pandu roga, hrillasa, mukha roga, kasa, svasa, agnimandhya, aruchi, meha, and kantharoga. Objective: The present study aimed to investigate the neuroprotective potential of “Himalayan Bayberry” (Myrica esculenta Buch.-Ham. ex D. Don) leaves methanol extract in Parkinson's disease induced by haloperidol. Materials and methods: The present investigation was completed in wistar rats, in which Parkinson's disease (PD) was induced with haloperidol 1 mg/kg, intraperitoneally. The rats were randomly divided into six gatherings and the test animals received the methanolic extract of M. esculenta (MEME) at a dose of 50, 100 and 200 mg/kg, orally for one week. Various behavioural, biochemical and histopathological parameters were estimated in haloperidol exposed rats. Results: MEME demonstrated significant and dose-dependent increment in behavioural activity and improved muscle coordination. The significant diminution in malonaldehyde level while improved the level of antioxidant enzymes like catalase, superoxide dismutase and reduced glutathione in extract treated group were observed as compared to the control group. Histopathological changes revealed MEME significantly reduced haloperidol-induced damage in the substantia nigra and there was very little neuronal atrophy. Conclusion: The outcomes showed the defensive role of M. esculenta against PD. The mechanism of protection may be due to an escalation of cellular antioxidants.